Short Term Clinical Outcome in Patients with Mitral Valve Replacement with or without Preservation of Subvalvular Apparatus - Husain, Sabrina Sharmeen; Ahmed, Chaudhury Meshkat; Mohmmad Sohan, Arif; Mahmud, Sohel; Rahman, Md Mustafizur; Zaman, SM Mustafa; Khaled, Md Fakhrul Islam; Osmany, DMMF (University Heart Journal, 2017)
Background: Preservation of subvalvular apparatus (SAP) during mitral valve replacement (MVR) was introduced about forty years back, but the outcome of this procedure is not well studied yet. Our study aimed to measure the in-hospital outcome of this procedure in rheumatic patients. Method: 44 patients of rheumatic heart disease undergoing for MVR in the department of cardiac surgery, BSMMU were enrolled for the study. The technique of SAP was according to choice of surgeon. Patients were divided into two groups- I) with preservation: complete preservation, where entire chordo-papillary apparatus was preserved & partial preservation, where posterior leaflet was preserved, II) no preservation: where subvalvular apparatus was completely excised. Surgical technique was different according to patients requirement and one of either technique was adopted by Fuster et al or Miki et al. Patients demographic profile and mitral valve status were recorded. Outcome was recorded in terms of hemoynamic outcome and in hospital death. Data was analyzed by Chi squired test. Result: Mean±SD of age of patients was 32±8 years, 29±7years in group-I, 36±9years in group-II. There was no significant difference in age distribution between two groups. Both groups were female predominant, 82% in group-I and 73% in group-II. Low cardiac output syndrome was observed in 4.5% of group-I and 32% in group-II (P-value was <0.001). Left ventricular failure was observed as 0% & 32% respectively (p value was <0.001). Inotropic agent was needed 45% & 75% respectively (p value was <0.01). In hospital death occurred in 4.5% & 13.5% in two groups respectively with no significant difference. Conclusion: Hemodynamic outcome and in hospital mortality was better when subvalvular apparatus was preserved during mitral valve replacement in rheumatic population. University Heart Journal Vol. 12, No. 1, January 2016; 3-7